Odpowiedź :
Odpowiedź:
A.
-3(1/2)=2 1/2 + 5
-3/2=7 1/2
-3/2=15/2
B.
-3(1/2)=-1/2 1/2+4
-3/2=-1/4+4
-3/2=15/4
Szczegółowe wyjaśnienie:
Hej!
a)
f(x) = 2x + 5
f(-3) = 2 * (-3) + 5 = -6 + 5 = -1
f(½) = 2 * ½ + 5 = 1 + 5 = 6
b)
f(x) = -½x + 4
f(-3) = -½ * (-3) + 4 = 1,5 + 4 = 5,5
f(1/2) = -½ * ½ + 4 = -¼ + 4 = 3¾
c)
f(x) = x - 2
f(-3) = -3 - 2 = -5
f(½) = ½ - 2 = -1½
d)
f(x) = x² + 3
f(-3) = (-3)² + 3 = 9 + 3 = 12
f(½) = (-½)² + 3 = ¼ + 3 = 3¼
e)
f(x) = -x² - x + 4
f(-3) = -(-3)² - (-3) + 4 = -9 + 3 + 4 = -2
f(½) = -(½)² - ½ + 4 = -¼ + 3½ = 3¼
Pozdrawiam! - Julka